Sundanese Taboo Words Avoidance Shaped By Myths In Batu Gara - Yogi Wijaya Lesmana; Nurhasanah Nurhasanah; Afni Apriliyanti Devita (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This research analyzes the avoidance strategies of taboo words in Batu Gara Village, Sumedang, through Roland Barthes’ semiotic theory of myth. A qualitative design was employed, with data collected through semi-structured interviews, participant observation, and document analysis involving five key informants and six villagers. The findings reveal that the myths embedded in taboo words such as Maung (tiger) and Péot (skinny) directly shape the community’s avoidance strategies. The belief in supernatural consequences (rain, lightning) naturalizes the myth, while historical normalization through generational transmission empties the reality of its history. The primary avoidance strategy of lexical substitution (e.g., Kerud for Maung) functions as a Barthesian ex-nomination to neutralize dangerous histories, while politeness rituals (punten) reinforce the myth’s authority. This research concludes that taboo word avoidance is not merely a linguistic prohibition but a semiotic performativity that perpetuates traditional ideology and social order.